Arcabouço jurídico normativo pedagógico da Lei federal 10.639/2003 na Universidade Federal de Uberlândia: avanços e limites - Silva, Glênio Oliveira da (2013)
This search addresses the public policies that directly or indirectly corroborate for the implementation of the Brazilian Law number 10.639/2003 in Federal University of Uberlândia and it analyzes the affirmative actions in this context. The study aims to answer some questions such as: Why we have found difficulties in implementing the Law 10.639/2003 and its correlate legislation in the institutions responsible for teachers formation, particularly in the courses of History, Visual Arts, Portuguese Language and Literature and Education teachers? We started from the hypothesis that implementing the Law 10.639/2003 is considered by popular movements that fight for the emancipation of black population and for its rights consider such actions as a form of eradicating racial and ethnic prejudice which are still present in our society. The methodology is based on case study, which allows the triangulation to other methodological approaches such as qualitative analysis and bibliographic search. The investigation instruments were: I. Bibliographic sources including books, papers, periodic and so one; II. Documental sources: specific legislation on the theme (Brazilian Federal Law 10.639/2003, Resolution CNE/CP 1/2004 and others; III. Oral sources obtained from semi structured interviews with coordinators of the selected Graduation courses. Critical multicuturalism according to McLaren (1999) allowed us to approach our research object in order to understand its plural characteristics, specially reading the different aspects that permeate the relationship between culture and identity, cultural differences and power relationship in modern society. In the study, we did not perceive the involvement of the Higher Education professionals in order to implement Law 10.639/2003. The problem perceived for implementing the law and its pedagogical normative legal framework is the personal and institutional attitude, because every subject involved in it has a direct responsibility. We cannot believe that the institutions may claim lack of knowledge and research in the area as impediments to implementing the disciplines and the pedagogical contents concerning to the Law nor contracting researcher experts and scholars on this topic to compose the frames of the University.